The Development of Sweet Taste: From Biology to Hedonics - Mennella, Julie A. (Rev Endocr Metab Disord, 2016)
From the age of two years, an American child is more likely to consume a sugar-sweetened product than a fruit or vegetable on any given day—a troubling statistic, given that food preferences are established early in childhood, as well as the strong association between this dietary pattern and increased risk of developing a number of chronic diseases. Here, we review the ontogeny and biopsychology of sweet taste, highlighting how a biological drive to prefer sweetness at high concentrations during childhood, which would have conferred an advantage in environments of scarcity, now predisposes children to overconsume all that is sweet in a modern food system replete with added sugars. We review the power of sweet taste to blunt expressions of pain and mask bad tastes in foods as well as factors that predispose some to consume high-sugar diets, including experiential learning and taste preferences driven in part by genetics. Understanding children’s unique vulnerability to our current food environment, rich in both nutritive and nonnutritive sweeteners, is highlighted as a priority for future research to develop evidence-based strategies to help establish healthy dietary behaviors early in life.